Analysis of Soft Switching Three Level Inverters - Bodur, Haci; Okumus, Hasan; Akboy, Erdem (IEEE, 2016)
This study represents a review of soft-switching three level (S3L) inverters. Inverters are classified two levels, three levels and multilevel inverters basically. Three level inverters that implicated as I or T types are used more commonly than the others. The aim of our study is to determine the advantages and disadvantages of the active and passive soft switching techniques at three level inverters.
Keywords: Engineering